Making a Medical School Class Whole: A Holistic Approach to Student Government. (June 2020) - Soled, Derek; Goel, Shivangi
Student government has a unique role in medical schools, where it can function to strongly nurture the well-being of a class. Student body representatives have a better understanding of the interests of medical students and the adversity they face. Thus, the student government is in a prime position to make positive change in the lives of their classmates with help from the school administration. This article explores these ideas and is written from the perspective of the co-presidents of the student body at a northeast medical school.